PENDIDIKAN PEREMPUAN PERSPEKTIP SYEKH RIFAAH AL TAHTAWI RELEVANSINYA DENGAN PENDIDIKAN PEREMPUAN DI INDONESIA - Sumaryati, Sumaryati; Hidayat, Muslih; Zuhri, Zuhri; Riyoko, Budi (Moderation | Journal of Islamic Studies Review, 2023)
This study discusses Women's Education from the perspective of Sheikh Rifaa Al Tahtawi its relevance to women's education in Indonesia. The purpose of this study is to find out the concept of Women's Education from Rifaah Al Tahtawi perspective and its relevance to women's education in Indonesia, This research is library research. Data collection techniques are carried out by documentation studies. The data analysis method uses content analysis. Content analysis is carried out by thoroughly reading Kitab Al-Murshid Al-Amīn Fi TarbiyAl Al-Banāt Wa AlBanīn, observing matters related to women's education in Kitab Al-Murshid AlAmīn Fi TarbiyAl Al-Banāt Wa Al-Banīn. Then how relevant is it to women's education in Indonesia, The results of the study concluded that women's education in Kitab Al-Murshid Al-Amīn Fi TarbiyAl Al-Banāt Wa Al-Banīn is: education should be treated fairly not necessarily differentiated by gender, the purpose of education is to get guidance to purify their souls, to obtain knowledge as a practice to improve the future and understand life in the family this not in line with functionalist structural theory. Its relevance to women's education in Indonesia is that the idea of implementing women's education is carried out by Indonesian women themselves and in its implementation has not been evenly distributed due to cultural barriers that give rise to forms of subordination, marginalization, stereotypes, violence against women, and double workload, so that the impact has not maximized the role of women in realizing the sense of patriotism of the country according to Rifaah Al Tahtawi's expectations.